Isolation and Analysis of Bioactive Compounds Endophytic Bacteria of Sea Fern (Acrtostichum aureum L.) from Bengkalis Island, Riau - Tetty Marta Linda; Azizul Berlyansah; Bernadeta Leni Fibriarti; Nery Sofiyanti; Silvera Devi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Endophytic bacteria have been known to produce high levels of secondary metabolites. The sterile leaves of the sea fern (Acrostichum aureum L.) contain many phytochemical compounds. This sea fern is often found in peat swamp areas. The aim of this study was to isolate, partial characterization, and analysis of bioactive compounds from endophytic bacteria of sea ferns to determine their bioactive compounds. Endophytic bacteria were isolated by a direct technique using nutrient agar (NA) media. In this study, the endophytic bacteria were characterized by macroscopic, microscopic, and Gram. Several tests were further performed, namely phytochemical test and Fourier Transform Infra Red (FT IR) FTIR tests from a crude extract of secondary metabolites of bacteria. The results of the isolation obtained six isolates of endophytic bacteria consisting of all isolates were Gram-negative. The phytochemical test results for the six isolates were positive for alkaloids and saponins but no steroids. Based on the results of phytochemical tests and FT IR, it is suspected that the isolate DSB 1.6 has similarities with the alkaloid functional group. This endophytic bacterial isolate can be developed as a candidate for produced of pharmacological compounds.